2015
DOI: 10.1002/eqe.2582
|View full text |Cite
|
Sign up to set email alerts
|

Intensity measures for probabilistic assessment of non‐structural components acceleration demand

Abstract: Summary A fundamental issue in the framework of seismic probabilistic risk analysis is the choice of ground motion intensity measures (IMs). Based on the floor response spectrum method, the present contribution focuses on the ability of IMs to predict non‐structural components (NSCs) horizontal acceleration demand. A large panel of IMs is examined and a new IM, namely equipment relative average spectral acceleration (E‐ASAR), is proposed for the purpose of NSCs acceleration demand prediction. The IMs efficienc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
24
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 26 publications
(24 citation statements)
references
References 26 publications
0
24
0
Order By: Relevance
“…One must nevertheless mention recent trends in building-specific vulnerability estimations that take into account the spectral content of the input motion around the building fundamental frequency (De Biasio et al 2015;Perrault and Guéguen 2015). The present work goes one step further along the same direction in considering also nonlinearities in the site response, but with a different approach as (a) it focuses on the damage differences between identical buildings located on a given site and on the reference rock, instead of considering only the "absolute" damage level, and (b) it considers multiple explanatory variables, mixing the rock loading level, site conditions and building characteristics through the peak ground acceleration on standard rock, a site amplification proxy and the ratio of elastic frequencies of building and soil, f struct /f soil .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…One must nevertheless mention recent trends in building-specific vulnerability estimations that take into account the spectral content of the input motion around the building fundamental frequency (De Biasio et al 2015;Perrault and Guéguen 2015). The present work goes one step further along the same direction in considering also nonlinearities in the site response, but with a different approach as (a) it focuses on the damage differences between identical buildings located on a given site and on the reference rock, instead of considering only the "absolute" damage level, and (b) it considers multiple explanatory variables, mixing the rock loading level, site conditions and building characteristics through the peak ground acceleration on standard rock, a site amplification proxy and the ratio of elastic frequencies of building and soil, f struct /f soil .…”
Section: Discussionmentioning
confidence: 99%
“…Concerning the former, the characteristics of seismic loading are generally derived from the code, i.e., based on very crude site classification, without specific attention to site frequency and associated amplification. Recent findings by De Biasio et al (2015) or Perrault and Guéguen (2015) have already concluded that the ground motion intensity offering the best correlation with damage in…”
Section: Introductionmentioning
confidence: 96%
“…The appropriate design safety factors for each expansion joint and adjacent building FIGURE 3 Analytical models of the adjacent buildings at which expansion joints were assumed at a height of 44 m model are determined based on the response database. 40 However, in the case of expansion joints where damage depends on the peak relative displacement between two buildings, IM should be sensitive to the peak relative displacement. 39 For IDA, the appropriate IM is essential to reduce the computational cost and variance of response.…”
Section: Intensity Measurementioning
confidence: 99%
“…Commonly used IMs are the peak ground acceleration (PGA), peak ground velocity (PGV), and spectral acceleration at the fundamental period. 40 However, in the case of expansion joints where damage depends on the peak relative displacement between two buildings, IM should be sensitive to the peak relative displacement. Tubaldi et al 28 studied the selection of an appropriate IM for the seismic pounding problem between two buildings and proposed the following intensity measure, noted by IM rel :…”
Section: Intensity Measurementioning
confidence: 99%
“…The question arises as to which IM is well correlated to the seismic demand on rigid blocks. From a performance-based earthquake engineering perspective, the identification of an efficient IM which is valid for a generic rigid block assumes a key role, as well as the assessment of fragility curves for loss assessment [24]. A fragility study of rigid blocks is therefore con-ducted aimed at two different objectives: (a) assessment of the most efficient IM; (b) influence of geometric properties of the rigid block on its performance.…”
Section: Fragility Analysismentioning
confidence: 99%